Peran Partisipasi Perangkat Desa Melalui Pelayanan Dalam Pelaksanaan Bantuan Langsung Tunai di Desa Bandar Khalipah - Utomo, Wahyu Wiji; Utami, Silvi; Isnaini, Akmalia Nur; Salwa, Zhafira; Ritonga, Abdul Rahman; Lubis, Muhammad Arham; Sinaga, Ichwan Pratama (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The village government is an element of government administration whose job is to serve the needs of the community. The village government has the duty and responsibility to manage the community in order to create a prosperous society. Based on Law Number 6 of 2014 concerning villages, it is stated that the village government is obliged to provide and improve services to the community and in carrying out its duties, the village government is obliged to carry out good administration and implement the principles of transparent village governance. Among the roles that must be carried out by Village Officials is serving the administrative needs of the community such as obtaining KTP, KK, Birth Certificates, resident certificates, letters of good behavior and so on. This study aims to describe and reveal village government services that occur in the Bandar Khalipah Village government office, as the main issue of how the role of the Village Government is in improving the distribution of Direct Cash Assistance services in Bandar Khalipah Village, Percut Sei Tuan sub-district, what are the obstacles faced by the Village Head in improving services at the Bandar Khalipah Village office in improving services to the community at the Bandar Khalipah Village Office, Percut Sei Tuan District, Deli Serdang Regency. This research uses qualitative research and data collection is done through observation, documentation and interviews. And the results of the research and conclusions: this shows that the performance of the Bandar Khalipah Village government is quite good in terms of productivity, service quality, responsiveness, responsibility and accountability in accordance with the provisions of the applicable laws and regulations and is supported by human resources and facilities and infrastructure adequate in carrying out the task. This can be seen in terms of service to the people of Bandar Khalipah Village. This can be realized because the Bandar Khalipah Village government is very obedient to regional regulations or policies and the direction of the Village Head. Keywords: village goverment, public service, BLT, Covid-19.